If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2x + -4) = -3(4x + -6) Reorder the terms: -5(-4 + 2x) = -3(4x + -6) (-4 * -5 + 2x * -5) = -3(4x + -6) (20 + -10x) = -3(4x + -6) Reorder the terms: 20 + -10x = -3(-6 + 4x) 20 + -10x = (-6 * -3 + 4x * -3) 20 + -10x = (18 + -12x) Solving 20 + -10x = 18 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 20 + -10x + 12x = 18 + -12x + 12x Combine like terms: -10x + 12x = 2x 20 + 2x = 18 + -12x + 12x Combine like terms: -12x + 12x = 0 20 + 2x = 18 + 0 20 + 2x = 18 Add '-20' to each side of the equation. 20 + -20 + 2x = 18 + -20 Combine like terms: 20 + -20 = 0 0 + 2x = 18 + -20 2x = 18 + -20 Combine like terms: 18 + -20 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| -(z+1)=-2(5-z) | | 2y-3x+11+10y-2x=180 | | x^2-27=-3x+1 | | 3-3[2-(6y-2)]= | | -3x-17+4x=x-5+x | | x^2-12x+44-9=0 | | 4[7-(y+2)]= | | -2x-10=180 | | 5(6x-4)+2=3(10x-20) | | 4(y-5)=16 | | 13-(-7x)+5x-(-10)= | | 2x^2-5x-52=0 | | -8y+4=20 | | (4x+7)=(3x-5) | | 2x^4+2x^4=4x^4 | | 5x+10y=70 | | 5y+8(y-5)+9= | | 10y-2x+5y-10=180 | | 2=x+10 | | 65y-64y-51=13 | | 2x^4+2x^4-4x^4=0 | | -14v=-112 | | (4u+36)(u^2+4u-12)=0 | | 103-4x=32x+15 | | 7x*21x=9408 | | 17b=85 | | 10-7x=180-42x | | 3(2x-1)+4x=5(3x-2)+4 | | 6(2x-4)=2(4x-6) | | 3x=6x-7 | | x-12=5x | | 2a-3a+4a=5a-18 |